2018
DOI: 10.3389/fpubh.2018.00173
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, Awareness, and Barriers Toward Influenza Vaccination Among Medical Doctors at Tertiary Care Health Settings in Peshawar, Pakistan–A Cross-Sectional Study

Abstract: Objective: This study intends to evaluate the knowledge, attitude and awareness of medical doctors toward influenza vaccination and the reasons for not getting vaccinated.Methods: A cross-sectional study was carried out among medical doctors in three major tertiary care health settings in Peshawar, Khyber Pakhtunkhwa (KP), Pakistan. A web-based, pre-tested questionnaire was used for data collection.Results: A total of (n = 300) medical doctors were invited, however only (n = 215) participated in the study with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 35 publications
6
24
2
Order By: Relevance
“…3 However, a Pakistani study conducted by Ali et al showed that the unfamiliarity with the vaccine, availability, and cost were the main reasons. 12 Moreover, an Indian study showed low acceptance due to the negative perceptions concerned with safety and efficacy. 13 Results from our model of regression analysis showed that HCWs who had never previously received the influenza vaccination were more likely to have negative perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, a Pakistani study conducted by Ali et al showed that the unfamiliarity with the vaccine, availability, and cost were the main reasons. 12 Moreover, an Indian study showed low acceptance due to the negative perceptions concerned with safety and efficacy. 13 Results from our model of regression analysis showed that HCWs who had never previously received the influenza vaccination were more likely to have negative perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively small number of HCWs in this study does not allow for subgroup analysis to delineate differences between nurses and physicians. A recent study in Pakistan showed low vaccination rates among physicians against influenza (8.84%), with lack of awareness about the vaccine and the recommendations being the major obstacles for adherence [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advice from doctors was also a key predictive factor of vaccination. Moreover, in the US, individuals with higher education, better income, and insurance coverage have higher vaccination rates [ 17 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a previous study, Asma et al (2016) reported that vaccination compliance was higher in PCPs with increased age and higher experience. Another study investigating healthcare professionals’ attitude to vaccination revealed that participants with higher experience were more likely to get vaccinated (Ali et al, 2018). Although our findings are conflicting with the results of many previous studies, some possible explanations could be derived regarding this controversy.…”
Section: Discussionmentioning
confidence: 99%